2011
DOI: 10.1016/j.healun.2011.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Sudden death after pediatric heart transplantation: Analysis of data from the Pediatric Heart Transplant Study Group

Abstract: BACKGROUND Sudden death is a well-recognized complication of heart transplantation. Little is known about the incidence and risk factors for sudden death following transplant in children. The purpose of this study was to determine the incidence of and risk factors for sudden death. METHODS Retrospective multi-center cohort study using the Pediatric Heart Transplant Study Group (PHTS) database, an event driven registry of children <18 years of age at listing undergoing heart transplantation between 1993 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 29 publications
(57 reference statements)
4
14
2
Order By: Relevance
“…This differs from prior studies in both adult and pediatric heart transplant recipients, which have shown an association between acute cellular rejection and sudden death [7,10,15]. Our study may not have found an association between rejection episodes and sudden death given our small sample size and the fact that our cohort as a whole did not have a high prevalence of either acute cellular or antibody mediated rejection.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…This differs from prior studies in both adult and pediatric heart transplant recipients, which have shown an association between acute cellular rejection and sudden death [7,10,15]. Our study may not have found an association between rejection episodes and sudden death given our small sample size and the fact that our cohort as a whole did not have a high prevalence of either acute cellular or antibody mediated rejection.…”
Section: Discussioncontrasting
confidence: 96%
“…The proportion of sudden death in our study cohort, 24%, is similar to prior studies, where sudden death was reported in 16-29% of heart transplant deaths [7,8,10]. To our knowledge, the hemodynamic differences we have shown between the SD group and the HFD/retransplant group are the first to be published in the literature.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Sudden death occurs in 1 out of 6 pediatric heart transplant recipients [34]. Factors associated with sudden death include: older recipient age, black race, and recurrent rejection within 1 year of age [33]. The development of cardiac allograft vasculopathy (CAV) accounts for approximately 14% of cases of death following pediatric heart transplantation [34].…”
Section: Coronary Artery Anomaliesmentioning
confidence: 99%